Low Serum Superoxide Dismutase Is Associated With a High Risk of Cognitive Impairment After Mild Acute Ischemic Stroke - Zhang, Ming-Si; Liang, Jian-Hai; Yang, Meng-Jia; Ren, Yue-Ran; Cheng, Dai-Hong; Wu, Qi-Heng; He, Yan; Yin, Jia (Frontiers in Aging Neuroscience, 2022)
Background: Poststroke cognitive impairment (PSCI) is a common complication after stroke, but effective therapy is limited. Identifying potential risk factors for effective intervention is warranted. Superoxide dismutase (SOD) plays a key role in stroke and neurodegenerative disorders. We investigated whether serum SOD levels were related to cognitive impairment after mild acute ischemic stroke (AIS) by using a prospective cohort design. Methods: A total of 187 patients diagnosed with mild AIS were recruited. Serum SOD, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and interleukin-6 (IL-6) levels were measured, and cognitive assessments (Mini-Mental State Examination, MMSE; Montreal Cognitive Assessment, MoCA) were performed in the early phase (within 2 weeks). These indexes and assessments were repeated at 3 months after onset. MoCA scores <22 in the early phase and at 3 months were defined as CI-E and PSCI, respectively. Results: In the early phase after mild AIS, 105 (56.1%) patients were identified as CI-E. Lower serum SOD was found in CI-E patients and was associated with higher inflammatory biomarkers (ESR, CRP and IL-6) and worse cognitive scores. A total of 103 stroke patients completed the 3-month follow-up, including 39 identified as PSCI. Serum SOD was consistently lower in PSCI patients at baseline and 3 months and positively associated with cognitive scores. In adjusted analyses, low serum SOD at baseline was independently associated with high risks of CI-E and PSCI, with odds ratios (ORs) of 0.64 and 0.33 per standard deviation increase in serum SOD, respectively. Multiple-adjusted spline regression models showed linear associations between serum SOD and CI-E (P = 0.044 for linearity) and PSCI (P = 0.006 for linearity). Moreover, 35.2% (19/54) of CI-E patients cognitively recovered during the 3-month follow-up. In multivariate analysis, SOD was identified as a protective factor for cognitive recovery after stroke (OR 1.041, 95% CI: 1.004-1.079, P=0.028). Conclusions: Low serum SOD after mild AIS was associated with high risks of cognitive impairment in the early phase and at 3 months, and increased SOD might be a protective factor for cognitive recovery after AIS.